Effect of fiber sizing on flexural properties of carbon fiber reinforced polypropylene composites - Lee, Ming Jie (Nanyang Technological University, 2022)
In this project, unidirectional carbon fiber (CF) was used to prepare the fiber reinforced polypropylene (PP) composite. Prior to composite preparation, PP was compounded with intumescent flame retardant (FR) additives. This project evaluated and compared the effectiveness of two different sizing agents: Joncryl U4190 and ethylene-methyl acrylate-glycidyl methacrylate (E-MA-GMA) copolymer. The unidirectional CF mats were coated with respective sizing agents via a simple solution dipping method after various surface treatments. The effectiveness and uniformity of the sizing agents were discussed in the results part. Functional groups present on the CF surface were identified by FTIR spectroscopy. TGA was utilised to determine the wt.% of the sizing agents and SEM analysed the morphology of the coated CF. Reinforced composites were prepared via hot-melt impregnation with the help of compression moulding press. Thereafter, three-point bending tests were carried out on the composite specimens prepared with and without fiber sizing. From the comparison of results, it was found that the fiber sizing has improved the flexural strength by 109.0 % and 72.46 % with the respective sizing agents in comparison to as-received CF mats. The shear strength has also been improved by 129.94% and 90.58% with the respective sizing agents.